2018
DOI: 10.1111/desc.12670
|View full text |Cite
|
Sign up to set email alerts
|

Training with a three‐dimensional multiple object‐tracking (3D‐MOT) paradigm improves attention in students with a neurodevelopmental condition: a randomized controlled trial

Abstract: The efficacy of attention training paradigms is influenced by many factors, including the specificity of targeted cognitive processes, accuracy of outcome measures, accessibility to specialized populations, and adaptability to user capability. These issues are increasingly significant when working with children diagnosed with neurodevelopmental conditions that are characterized by attentional difficulties. This study investigated the efficacy of training attention in students with neurodevelopmental conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 42 publications
5
36
0
Order By: Relevance
“…This study demonstrated that repeated practice on the MOT paradigm improved performance by a standardized change of 0.62 (i.e., 41% increase as reported in the paper) after 15 sessions. The data from Tullo, Guy et al (2018) suggests an improvement as early as four sessions. Moreover, Faubert (2013) demonstrated that the learning rates for MOT differed across levels of athleticism in a typically developed adult population.…”
Section: Study 2: Feedback and Learningmentioning
confidence: 91%
See 3 more Smart Citations
“…This study demonstrated that repeated practice on the MOT paradigm improved performance by a standardized change of 0.62 (i.e., 41% increase as reported in the paper) after 15 sessions. The data from Tullo, Guy et al (2018) suggests an improvement as early as four sessions. Moreover, Faubert (2013) demonstrated that the learning rates for MOT differed across levels of athleticism in a typically developed adult population.…”
Section: Study 2: Feedback and Learningmentioning
confidence: 91%
“…Previous research has examined the change in MOT capability across multiple sessions ( Faubert, 2013 ; Legault, Allard, & Faubert, 2013 ; Tullo, Guy, Faubert, & Bertone, 2018 ). Although the current study is the first to isolate the effect of feedback on MOT performance, the aforementioned studies demonstrated a learning effect for MOT with the inclusion of feedback.…”
Section: Study 2: Feedback and Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…attention, inhibitory function, cognitive flexibility, working memory) due to their involvement in higher-level cognitive tasks [6,9,35]. PCT has been shown to improve different cognitive abilities in both healthy and pathological populations of young and old adults [34,36,37]. It was postulated that PCT may reduce or reverse the age-related cognitive decline and the aim of this study is to verify if PCT can enhance cognition in older adults with SCD.…”
Section: Introductionmentioning
confidence: 99%